The Influence of Service and Prices on Consumer Decisions in Buying Products at the X Second Wear Store - Mintawati, Hesri; Desianti, Lisa Chandrasari; Solihah, Siti Sa'adiatus; Putri, Desti Amelia; Laksana, M. Agung (Neolectura, 2024)
This research aims to analyze the influence of service and price on consumer decisions in purchasing products at Toko X Second Wear, a quality used clothing shop. Using a qualitative approach, data was collected through in-depth interviews with ten consumers who had shopped at the store. The research results show that responsive and empathetic service from shop staff and competitive prices greatly influence consumer satisfaction and purchasing decisions. Consumers appreciate the friendliness, politeness and speed of service of the staff, which significantly improves their shopping experience. Apart from that, the price of the product which is considered commensurate with its quality is also an important factor in purchasing decisions. This study suggests that Toko X Second Wear should improve the clarity of promotions and loyalty programs to better satisfy customers. The findings of this research can be a guide for other used clothing store managers in improving marketing and service strategies to increase customer satisfaction and loyalty.